Abyssal hills: influence of topography on benthic foraminiferal assemblages - Stefanoudis, P; Bett, B; Gooday, A (Elsevier, 2016)
Abyssal plains, often thought of as vast flat areas, encompass a variety of terrains including abyssal hills, features that constitute the single largest landscape type on Earth. The potential influence on deep-sea benthic faunas of mesoscale habitat complexity arising from the presence of abyssal hills is still poorly understood. To address this issue we focus on benthic foraminifera (testate protists) in the >150-μm fraction of Megacorer samples (0–1 cm layer) collected at five different sites in the area of the Porcupine Abyssal Plain Sustained Observatory (NE Atlantic, 4850 m water depth). Three sites are located on the tops of small abyssal hills (200–500 m elevation) and two on the adjacent abyssal plain. We examined benthic foraminiferal assemblage characteristics (standing stock, diversity, composition) in relation to seafloor topography (hills vs. plain). Density and rarefied diversity were not significantly different between the hills and the plain. Nevertheless, hills do support a higher species density (i.e. species per unit area), a distinct fauna, and act to increase the regional species pool. Topographically enhanced bottom-water flows that influence food availability and sediment type are suggested as the most likely mechanisms responsible for these differences. Our findings highlight the potential importance of mesoscale heterogeneity introduced by relatively modest topography in regulating abyssal foraminiferal diversity. Given the predominance of abyssal hill terrain in the global ocean, we suggest the need to include faunal data from abyssal hills in assessments of abyssal ecology.